En-block cytoreduction for advanced ovarian cancer - Anastasios Pandraklakis; Vasilis Mitsopoulos; Ioannis Biliatis (Elsevier, 2023)
The standard treatment of advanced ovarian, fallopian tube and peritoneal cancer is cytoreductive surgery followed by platinum-based chemotherapy (du Bois et al., 2005). This type of cancer expands through the peritoneum, which is the thin and continuous epithelial layer covering the abdominopelvic cavity and abdominal organs. Several separate procedures in the lower and upper abdomen are necessary for complete cytoreduction (Phillips et al., 2018). Considering the continuity of the peritoneum, these procedures could potentially take the form of an en-block specimen (Kalra et al., 2021). This approach is technically quite challenging and needs excellent understanding of the anatomy.Our aim is to present the feasibility of removing one en-block specimen, composed of multiple excisions and to propose an intraoperative strategy on how to perform such a dissection.This video demonstrates an en-block primary cytoreduction in a 62-year-old patient with stage IIIC ovarian cancer (FIGO) who underwent laparotomy, right diaphragmatic stripping, Morrison's pouch and right abdominal peritonectomy, radical omentectomy, splenectomy and modified posterior exenteration with end-to-end rectosigmoid anastomosis. End result was complete cytoreduction and final histology showed high grade serous carcinoma.The postoperative period was uneventful, and the patient was discharged on day 6. She completed 6 cycles of carboplatin and paclitaxel chemotherapy and is free of disease 32 months later.In conclusion, this approach follows the dissemination pattern of ovarian cancer and allows for a better understanding of the anatomy of the peritoneum. We propose that en-block excisions might be particularly useful for the training of young Gynaecological Oncologists in order to enhance their knowledge of the anatomy and their surgical skills.